Digital Religious Discourse: Constructing Legitimacy and Counter-Narratives in Islami.co - Ats Tsaqofi, Waki; Satori, Achmad; Mahmudah, Sarah Hajar; Saehudin, Akhmad; Abshar, Ulil; Li, Wenhua (Center for Research and Publication (PUSLITPEN), UIN Syarif Hidayatullah Jakarta, 2025)
Digital controversies around Al-Māʾidah 5:51 and the Ahok case have sharpened struggles over Qur’anic authority in Indonesia’s public sphere. This article examines how the progressive portal Islami.co constructs religious legitimacy and counter-narratives in this context. Using qualitative critical discourse analysis, it analyzes fourteen opinion and expository articles on verse politicization, Qur’an translation, and digital daʿwah, applying Fairclough’s three-dimensional model and van Leeuwen’s legitimation categories. The study finds three mechanisms of legitimation: (1) semantic reframing of key terms such as awliyāʾ/wali; (2) intertextual authority through selective use of classical tafsīr, fiqh, and contemporary scholarship; and (3) moral evaluation foregrounding justice, maṣlaḥah, and plural coexistence. These strategies underwrite counter-narratives that decouple voting for non-Muslim leaders from accusations of betrayal, critique terjemahisme and post-truth uses of state translations, and oppose Islam marah with an ethic of Islam ramah. The findings show how progressive Islamic counter-publics linguistically contest conservative monopolies over Qur’anic discourse.